Detection of Surface Defects on Compact Discs. (16th October 2007) - Odgaard, P. F.; Stoustrup, J.; Andersen, P.
Abstract : Online detection of surface defects on optical discs is of high importance for the accommodation schemes handling these defects. These surface defects introduce defect components to the position measurements of focus and radial tracking positions. The respective controllers will accordingly try to suppress these defect components resulting in a wrong positioning of the optical disc drive. In this paper, two novel schemes for detecting these surface defects are introduced and compared. Both methods, which are an extended threshold scheme and a wavelet packet-based scheme, improve the detection compared with a standard threshold scheme. The extended threshold scheme detects the four tested defects with a maximal detection delay of 3 samples while the wavelet packet-based scheme has a maximal detection delay of 6 samples. Simulations of focus and radial positions in the presence of a surface defect are performed in order to inspect the importance and consequences of the size of the detection delay, from which it can be seen that focus and radial position errors increase significantly due to the defect as the detection delay increases.